Assessing Cooperative Contributions to Economic Sustainability in Karnali Province, Nepal (The Harvest, 2026)
The Karnali Province, the most economically open and geographically isolated region in Nepal has seen the emergence of cooperatives as a significant institution of savings mobilization, low-cost credit and income earning potential where the traditional modes of development have proven ineffective in most instances. The survey method is used to assess the impact of cooperatives in supporting the sustainability of the economy in Karnali in this study. The quantitative data collected by means of structured questionnaires included 384 cooperative members in Surkhet districts. The results demonstrate great improvement: average household income increased by 58.9% (NPR 11,200 to NPR 17,800), savings rose by 131.4% (NPR 3,500 to NPR 8,100), the access to credit grew by 28.4-73.2% and the level of employment was improved by 46.0 to 68.0%. Many of the interviewees mentioned enhanced financial inclusion, training capacity and livelihood security. The correlation analysis showed that there were strong positive correlations between cooperative participation and economic outcomes particularly among the long-term members. The cooperative model despite the obstacles of small-size loans and technical assistance proved to be effective in facilitating the grassroot development and financial empowerment of marginalized communities. The paper finds that cooperatives can play a significant role in achieving economic sustainability in rural Nepal, and it is advisable to enhance their policy and institutional backing to create maximum impacts.